Purulent-Inflammatory Complications During Transurethral Resection of Benign Prostatic Hyperplasia: Role of The Use of Laser and Magnetic Radiation - Magdalena E. Seidl, Dominik M. Mayer, Elias K. Haas (Academic Journal of Clinicians, 2025)
It has been established that the most effective preoperative preparation method is the combination of transrectal magnetic therapy and transurethral laser therapy. This proposed method activates the immune system, achieves urine sterility in 26.7% of cases, prostate tissue sterility in 37.8% of cases, and improves prostate tissue microcirculation, significantly reducing the incidence of purulent-inflammatory and thrombohemorrhagic complications and shortening the postoperative hospital stay. The positive effects of magnetic therapy, laser therapy, and their combination on key immune parameters, bacterial counts in urine and prostate tissue, prostate microcirculation, and their impact on the postoperative period were studied for the first time. Transrectal magnetic therapy was found to eliminate T-cell immunity deficiency, increase B-lymphocyte activity and neutrophil phagocytic capacity, reduce endogenous intoxication, but have no effect on humoral immunity. Prostate vascular elasticity and tone are normalized. Transurethral laser therapy eliminates B-cell immunity deficiency and reduces endogenous intoxication, but T-cell immunity deficiency persists. A decrease in the resistance index indicates a decrease in peripheral vascular resistance in the prostate. The species composition of urine and prostate tissue was studied, revealing a nearly 100% infection rate. It has been established that in patients with BPH, gram-negative bacteria predominate among the isolated pathogenic microflora, and in some cases the microflora of urine and prostate tissue is not identical. The purpose of the study, is to improve the results of transurethral resection in patients with benign prostatic hyperplasia. To achieve this goal, the following tasks were set and solved; To study the influence of traditional preoperative preparation, magnetic therapy, laser therapy and their combination on existing changes in the immune system and indicators of vascularization and hemodynamics of the prostate gland. To determine the microbial titer of urine microflora and the species characteristics of isolated urostomes and prostate tissue microflora. To study the effects of various treatment methods on these parameters and to Conduct a comparative analysis of the obtained results and characteristics of the postoperative period in patients with BPH against the background of various types of preoperative preparation.